Waqf Problems in Literature Context - Puspita, Amelia Tri (Islamic Social Finance, 2025)
This study aims to analyze research trends and research paths that appear in the literature related to waqf problems. This study uses a bibliometric approach with the VosViewer analysis tool to identify patterns of co-authorship, institutional collaboration, and co-emergence of keywords. The results of the study show stable research growth. The co-authorship analysis revealed a network of collaboration between authors and institutions, with Malaysia and Indonesia emerging as the main contributors, with the authors contributing the most namely Omar Mohammed S, Moh'd I.S., Saiti B, Bulut M, Korkut C.E.M, Dambele A, Omar Mohammed, and Mohammad M.O. Meanwhile, the organizations that have the most authors in journals themed Waqf problems are, Hebrew University of Jerusalem, University of Tunisia, Princeton University, and Department of Arabic Studies. Then, keyword analysis shows that the literature is dominated by fundamental themes that view waqf as a philanthropic and asset-based institution, while more recent studies increasingly focus on governance reform, cash waqf, Islamic financial integration, social entrepreneurship, technology utilization, and green waqf.